Development and Plasticity of Cognitive Flexibility in Early and Middle Childhood - Buttelmann, Frances; Karbach, Julia (Frontiers in Psychology, 2017)
Cognitive flexibility, the ability to flexibly switch between tasks, is a core dimension of executive functions (EFs) allowing to control actions and to adapt flexibly to changing environments. It supports the management of multiple tasks, the development of novel, adaptive behavior and is associated with various life outcomes. Cognitive flexibility develops rapidly in preschool and continuously increases well into adolescence, mirroring the growth of neural networks involving the prefrontal cortex. Over the past decade, there has been increasing interest in interventions designed to improve cognitive flexibility in children in order to support the many developmental outcomes associated with cognitive flexibility. This article provides a brief review of the development and plasticity of cognitive flexibility across early and middle childhood (i.e., from preschool to elementary school age). Focusing on interventions designed to improve cognitive flexibility in typically developing children, we report evidence for significant training and transfer effects while acknowledging that current findings on transfer are heterogeneous. Finally, we introduce metacognitive training as a promising new approach to promote cognitive flexibility and to support transfer of training.